The Effort of Caring: The Caregivers’ Perspective of Dual Sensory Impairment - Dunsmore, Moira E.; Schneider, Julie; McKenzie, Heather; Gillespie, James A. (Frontiers in Education, 2020)
Abstract Aim: To explore the social implications of Dual Sensory Impairment (DSI) for older Australian adults and their family carers. Background: DSI in older adults is a chronic progressive disability with varying combined degrees of vision and hearing loss. Prevalence increases with age and is particularly high in those > 85 years of age. Older persons with DSI experience a range of functional, social and emotional health issues and are considered a vulnerable group. Family carers fulfil complex multiple roles and provide the majority of care and support to this group. Caregiving and care-receiving are reported as demanding and stressful for both. Together, both spousal and mother-daughter dyads experience a range of social consequences as a result of DSI which are under-reported in the DSI literature. Design: Qualitative study design using Grounded Theory Methodology (GTM). Methods: A series of 23 qualitative in-depth interviews with older Australians with DSI and their family carers were conducted over eighteen months. Data were analysed using the inductive constant comparative method to systematically categorise emergent themes in order to develop a grounded theory. Findings: This qualitative study explored the shared social experiences of the family carer and care-receiver in the context of DSI and identified social isolation, social effort and negotiating relationships as key themes. These common social effects interrupt personal and external social networks and have a pervasive, often negative impact on the social relations of each individual within the dyadic relationship as well as their external relationships. Conclusion: The experience of living with DSI is underexplored from a dyadic perspective. Few studies explore the perspective of both family carer and their family member with DSI. This report draws on the experiences of the family carers and identifies three main themes that impact the quality of their dyadic relationship. While caring in a DSI context has clear parallels to caring in other health domains, the social relational aspects of DSI appear unique justifying further qualitative exploration of the dyadic perspective. Keywords: dual sensory impairment, deafblind, ageing, social exclusion, social support, family carers, dyad.